Intellectual property information literacy education: evidence from 30 Chinese National IP Demonstration Universities - Yuan Liu; Yuqi Zhao (Humanities & Social Sciences Communications)
Abstract Intellectual property (IP) information literacy is crucial for both personal development and national innovation. China has implemented many supportive policies in this field. Nevertheless, existing research on how Chinese universities implement this type of education—particularly their distinctive approaches and the challenges they face—remains limited. This study conducts a comprehensive analysis in this critical yet under-researched area by introducing a specific definition of “IP information literacy” as an independent concept and investigating its educational status at 30 Chinese National IP Demonstration Universities, which are higher education institutions jointly selected by CNIPA and MOE in 2020 for their outstanding performance in IP education and management. Using web-based research supplemented by email surveys, we collected extensive data on courses, IP databases, and learning resources. Our findings reveal that IP information literacy education has gained significant attention and manifests in diverse forms, with content primarily focused on patents. However, our study identified several challenges, including inadequate accessibility, insufficient systematization, disparities in inter-library IP resources, and widespread disorganization of internal access pathways. We recommend tailoring courses for different academic majors, developing a systematic and coherent course framework, and enhancing library IP information resources and access. This research deepens the understanding of IP information literacy education in Chinese universities and offers valuable insights for policymakers and scholars.